Effect of Extraction Time Microwave-Assisted Solvent Extraction (MASE) Method on Decaffeination of Robusta Coffee (Coffea canephora) Java Ijen - Prasiska, Revina Lusy; Yuniati, Yuyun; Hariyani, Nunuk; Hartati, Fadjar Kurnia (Indonesian Journal of Food Technology, 2025)
Java Ijen robusta coffee is one of the potential coffee types to be developed as a low-caffeine product for sensitive consumers. The decaffeination process aims to reduce caffeine levels without eliminating the sensory characteristics of coffee. This study aims to determine the effect of variation in extraction time using the Microwave-Assisted Solvent Extraction (MASE) method on caffeine recovery, chlorogenic acid content, and organoleptic quality of coffee drinks. The extraction process uses water solvent and microwave power of 450 watts with time variations R1 = 4 minutes, R2 = 8 minutes, R3 = 12 minutes, R4 = 16 minutes, and R5 = 20 minutes. Analysis of caffeine content was carried out using a UV-Vis spectrophotometer, while chlorogenic acid content was determined by the titration method. Organoleptic assessment included colour, acidity and aroma attributes by 25 untrained panelists using median scores. The results showed that extraction time significantly affected caffeine recovery and chlorogenic acid content. The highest caffeine recovery of 57.34% and chlorogenic acid content of 19.19% were obtained at an extraction time of 20 minutes. The most preferred colour and acidity were also found in the 20-minute treatment, while the best aroma was at 12 minutes. Increasing extraction time increased colour intensity, acidity, and caffeine and chlorogenic acid concentrations. These results demonstrate the potential of the MASE method as an efficient alternative in decaffeinating robusta coffee while maintaining sensory quality.